2017
DOI: 10.1159/000454960
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Volume after Laparoscopic Low Anterior Resection Predicts Anastomotic Leakage

Abstract: Background/Aim: Anastomotic leakage (AL) is a major complication after laparoscopic low anterior resection (Lap-LAR). Many surgeons encounter AL following severe postoperative diarrhea. However, little is known about the relationship between postoperative fecal volume and AL. This study determined whether postoperative fecal volume can predict AL. Methods: A retrospective assessment was performed with data from 176 patients with rectal cancers who underwent Lap-LAR between April 2011 and August 2015. A transan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…The intraluminal pressure at the anastomotic site might increase when a lot of watery stool fills the remnant rectum, causing anastomotic disruption. There are only a few reports discussing the relationship between early postoperative diarrhea and AL after LAR [24][25][26] . Hidaka et al concluded that a fecal volume of ≥118 mL for 3 days after surgery may be a reliable predictor of the development of AL 24) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intraluminal pressure at the anastomotic site might increase when a lot of watery stool fills the remnant rectum, causing anastomotic disruption. There are only a few reports discussing the relationship between early postoperative diarrhea and AL after LAR [24][25][26] . Hidaka et al concluded that a fecal volume of ≥118 mL for 3 days after surgery may be a reliable predictor of the development of AL 24) .…”
Section: Resultsmentioning
confidence: 99%
“…There are only a few reports discussing the relationship between early postoperative diarrhea and AL after LAR [24][25][26] . Hidaka et al concluded that a fecal volume of ≥118 mL for 3 days after surgery may be a reliable predictor of the development of AL 24) . Ito and Hiraki et al reported that early postoperative diarrhea, defined as at least 1 passage of more than approximately 50 mL of watery stools within 7 days after surgery, was associated with AL 25,26) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diarrhoea has also been reported as a potential risk for anastomotic leakage in recent years. Hidaka et al [ 26 ] demonstrated that a faecal volume over 118 ml within 3 days after colorectal surgery may be a reliable predictor for anastomotic leakage. Li et al [ 44 ] found that the incidence of anastomotic leakage was higher in patients with early postoperative diarrhoea after rectal cancer surgery than in those without (16.2% vs. 5.2%, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative symptoms or clinical features, such as early postoperative diarrhoea [ 26 ], and hypoalbuminemia [ 27 ], that might be associated with outcomes were also recorded. Early postoperative diarrhoea was defined as three or more unusually loose or liquid stools per day [ 28 ], occurring within 7 days after surgery.…”
Section: Methodsmentioning
confidence: 99%